2011
DOI: 10.1097/yct.0b013e3182182be0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Repeated Etomidate Anesthesia on Adrenocortical Function During a Course of Electroconvulsive Therapy

Abstract: Etomidate and propofol would not affect the adrenocortical function during ECT, and hemodynamics reached normal level in a short time after ECT. Etomidate and propofol were both safe intravenous anesthetics during ECT, although etomidate was associated with comparatively longer seizure duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…Although the study supports the hypothesis that the combined use of etomidate and propofol reduces the side effects of etomidate and propofol with minimal effects on safety and recovery, a larger trial that is sufficient to detect differences is needed to confirm these findings before a change in clinical practice is recommended. Secondly, although plasma corticosteroid concentrations were not recorded in the current study, a number of studies have demonstrated that the induction dose of etomidate can decrease plasma corticosteroid concentrations, and that this can be sustained for 6-8 h, leading to adrenocortical dysfunction (24)(25)(26). Thirdly, only the short-term hemodynamic effects on elderly patients were investigated.…”
Section: A B Cmentioning
confidence: 99%
“…Although the study supports the hypothesis that the combined use of etomidate and propofol reduces the side effects of etomidate and propofol with minimal effects on safety and recovery, a larger trial that is sufficient to detect differences is needed to confirm these findings before a change in clinical practice is recommended. Secondly, although plasma corticosteroid concentrations were not recorded in the current study, a number of studies have demonstrated that the induction dose of etomidate can decrease plasma corticosteroid concentrations, and that this can be sustained for 6-8 h, leading to adrenocortical dysfunction (24)(25)(26). Thirdly, only the short-term hemodynamic effects on elderly patients were investigated.…”
Section: A B Cmentioning
confidence: 99%
“…A clear limitation of this assessment is the assumption that the clinical efficacy of ECT depends solely on the electrical length of the evoked seizure, when there is no evidence that this assumption is true ( Fear et al, 1994 ; Geretsegger et al, 1998 ; Sackeim, 1999 ; Azuma et al, 2007 ; Bauer et al, 2009 ; Stewart, 2012 ; Martinez-Amoros et al, 2014 ). In fact, different values for the lower limit of the electrical convulsion can be found in the literature: 15 s ( Gonzalez et al, 2007 ), 20 s ( Bertolin-Guillen et al, 2006 ; Ramirez-Segura and Ruiz-Chow, 2013 ), 25 s ( Nguyen et al, 1997 ; Dogan et al, 2011 ; Gombar et al, 2011 ; Hizli Sayar et al, 2014 ; Martinez-Amoros et al, 2014 ), and 26 s ( Wang et al, 2011 ). These data preclude us from directly comparing the percentage of sessions that were considered ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…In der o. g. Fachinformation wird vor einer kontinuierlichen Infusion oder wiederholten Verabreichungen von Etomidat gewarnt, da als direkte Folge eine prolongierte Suppression des endogenen Kortisols und Aldosterons auftreten kann. Zwar fanden einige Autoren [95][96][97] keinen solchen Zusammenhang, allerdings stellten Kogan-Goloborodko und Grözinger [98] den Fall eines Patienten vor, bei dem im Rahmen einer hochfrequenten EKT-Behandlungsserie mit täglichen Sitzungen unter Etomidat-Narkosen ein sukzessiver Abfall des Kortisolspiegels beobachtet werden konnte. Dieser lag erstmalig am 10 Behandlungstag unterhalb des Normwertes, erholte sich dann aber wieder rasch.…”
Section: Etomidatunclassified